THE ANALYSIS OF READING TEXT AND THE EXERCISES IN "ENGLISH FOR JUNIOR HIGH SCHOOL" USED IN THE FIRST YEAR OF JUNIOR HIGH SCHOOL - ISMAWATI, RITA SITI (2007)
This study aims at describing the kinds of reading text and comprehension questions of the textbook English for Junior High School and analyzing whether the reading texts and comprehension questions are appropriate with Nutall's Taxonomy or not. The type of the study is descriptive qualitative study. The object of this study is the reading text and reading questions presented in of the English textbook used in first year students of Junior High School. In this research, the writer finds that the reading text and the comprehension questions of the textbook entitled "English for Junior High School" are developed by Nutalls taxonomy. This textbook contains only seven questions that belong to yes/no question, sixteen questions belong to Wh-question and five questions belong to true or false. It is good because it has score 57,14% for the Wh-question, score 25% for the yes/no questions and 17,85% for the true of false question. It means that the textbook is compatible with the Nutall's taxonomy. The writer concludes that the compatibility of the "English for Junior High School" textbook is good. The textbook can be used by the students of the first year of Junior High School although the textbook still needs to be improved and revised.